Association of non-Alcoholic Fatty Liver Disease with Urolithiasis detected on non-Contrast Computed Tomography - Kamil Abdulmajeed Ahmed; Saeed Nadhim Younis (Advanced Medical Journal)
Background & Objectives: We aimed to assess whether there is an association between urolithiasis and non-alcoholic fatty liver disease using non-enhanced computed tomography.